O programa garantia-safra como política de desenvolvimento rural sustentável no semiárido: o caso de Feira de Santana (BA) - Bulhões, Igor Santos (2022)
The recurrent phenomenon of droughts in the semi-arid region was historically seen by the State as a national tragedy, which favored the consolidation of the so-called “drought industry” by the regional agrarian elites, as opposed to the paradigm of coexistence with the semi-arid region, guided by peasants, movements, organizations and partner institutions. In this context, pressured by the demands of social movements and trade unions in the countryside regarding the need to create an agricultural insurance suitable for the reality of family farming located in the semiarid region, Garantia-Safra was created in 2001. The objective of this work was to to assess the capacity of this policy to act as an inducer of sustainable rural development, through appropriate agriculture for populations located in the semi-arid environment of the municipality of Feira de Santana (BA). The methodological approach is to carry out an analysis of the social formation of the peasantry and family farming in the semi-arid region to understand their singularities, vulnerabilities and historical debts of the Brazilian State with the category. A study was also carried out on the structuring of the Garantia-Safra to understand its working mechanisms and possibilities for improvement. Finally, discussions were held on important elements for sustainable rural development in the semiarid region based on participatory frameworks, social control, integration with other sectoral public policies, agricultural income, agronomic performance, food and water sovereignty. Official data showed a high rate of occurrence of claims, indicating difficulties in financial self-sustainability and in expanding the number of program quotas, as well as a low ability to adapt to the semi-arid environment on the part of family units adhered to the program. These weaknesses are further reinforced by structural problems such as the lack of land tenure regularization and the growing mini-fundarization of family production units, as well as the residual effect of other complementary sectoral public policies, such as credit and the provision of technical and technical assistance services and rural extension. The lack of direct incentives from Garantia-Safra for productive restructuring, in order to dilute the risks associated with agricultural activities, and increase the resilience of local agroecosystems, was one of the main obstacles encountered in the promotion of sustainable rural development. In this sense, the Garantia-Safra program proved to be more related to an emergency program to mitigate the effects of droughts and to transfer income to the poorest family farmers who are vulnerable to the effects of climate variability typical of the Brazilian semi-arid environment and global climate change.